Outpatient Endovascular Tibial Artery Intervention in an Office-Based Setting Is as Safe and Effective as in a Hospital Setting. (December 2018) - D'Souza, Steve M.; Stout, Christopher L.; Krol, Emilia; Dexter, David J.; Ahanchi, Sadaf Sadie; Panneton, Jean M.
Purpose: To compare outcomes of outpatient tibial artery procedures between an office endovascular center and a hospital angiography suite.Methods: A retrospective review was conducted of 204 outpatient tibial interventions performed on 161 patients (mean age 72±11.5 years; 81 men) in either an office (n=100) or hospital (n=104) angiography suite from April 2011 through September 2013. Patients who had an existing ipsilateral bypass that was completely proximal to the tibial trifurcation were eligible, as were patients with prior proximal endovascular interventions. Exclusion criteria included previous ipsilateral bypass involving the infrapopliteal vessels, in-patient status at the time of the procedure, planned admission after the procedure, and infrapopliteal stenting. Treatment included percutaneous transluminal angioplasty (PTA) or PTA with atherectomy. Primary outcomes were unplanned admission, emergency room visits, acute complications, and patency.Results: There were no significant differences in demographics or baseline Rutherford category between patients treated in an office endovascular suite vs a hospital angiography suite. Factors more prevalent in the hospital group included chronic obstructive pulmonary disease (16% vs 8%, p=0.045), renal insufficiency (37% vs 25%, p=0.017), and previous proximal bypass (12% vs 4%, p=0.045). Of the 100 office procedures, 25 involved PTA and 75 were PTA with atherectomy, while in the 104 hospital procedures, PTA was applied in 68 patients and PTA with atherectomy in 36. Thirty-day local complication rates (7% vs 11%, p=0.368), systemic complication rates (4% vs 8%, p=0.263), and mortality (1% vs 2%, p=0.596) in the office vs hospital setting were not statistically different. Unplanned postprocedure hospital admission rates for medical reasons were lower in the office group (2% vs 11%, p=0.01). Kaplan-Meier estimates of the 1-year follow-up data were better in the office group for primary patency (69% vs 53%, p=0.050), assisted primary patency (90% vs 89%, p=0.646), and amputation-free survival (89% vs 83%, p=0.476), but the differences were not statistically significant.Conclusion: Efficacy and safety of outpatient endovascular tibial artery interventions between office and hospital settings were similar, with lower unplanned admission rates and better patency. With appropriate patient selection, the office endovascular suite can be a safe alternative to the hospital angiography suite.